Two-Hour Sea Level Oscillations in Halifax Harbour - Dan Kelley; Clark Richards; Ruby Yee; Alex Hay; Knut Klingbeil; Phillip MacAulay; Ruth Musgrave (Journal of Marine Science and Engineering, 2025)
Halifax Harbour, a major seaport in Nova Scotia that is approximately 100 km southeast of the Bay of Fundy, comprises a deep inner region called Bedford Basin, connected to the adjacent ocean by a shallow channel called The Narrows. A study of sea level and currents reveals the presence of episodic oscillations in The Narrows, with a period of approximately 2 h. The oscillation strength varies from day to day and, to some extent, through the seasons. The median amplitude of the associated sea level variation is 18% that of the de-tided signal, rising to 32% at the 95-th percentile. Values this large may be of concern for the transit of deep-draft vessels through shallow parts of the harbour and for the clearance of tall vessels under the two bridges that span The Narrows. Another concerning issue is the matter of oscillations being superimposed on storm surges. In addition to such direct effects of sea level variation, shear associated with the oscillations may increase the turbulent mixing in the region, affecting the overall state of this estuarine system. We explore the nature of the oscillations as a first step towards the improvement of prediction schemes for sea level and currents in the region. This involves an analysis of the oscillations in the context of seiche and Helmholtz resonance theories and the use of a 2D numerical model to handle realistic bathymetric conditions and other complications that the simpler theories cannot address. We conclude that the predictions of Helmholtz resonance theory are in reasonable agreement with both the observations and the predictions of the numerical model.

A Systematic Review of Oceanic-Atmospheric Variations and Coastal Erosion in Continental Latin America: Historical Trends, Future Projections, and Management Challenges - Ruby Vallarino-Castillo; Vicente Negro-Valdecantos; José María del Campo (Journal of Marine Science and Engineering, 2024)
The intricate interplay of oceanic-atmospheric variations has intensified erosive processes on sandy beaches in recent decades, with climate change expected to exacerbate these impacts in the future. Projections for the southern Atlantic and Pacific regions of continental Latin America predict increased extreme events and heightened impacts on sandy beaches, highlighting disparities in studies addressing coastal erosion and its causes. To address these risks, a systematic review is proposed to analyze historical trends and projections, aiming to inform local-level studies and management strategies for at-risk coastal communities. Reviewing 130 research papers, insights reveal the influence of climatic events like El Niño and La Niña on coastal dynamics, as well as the effects of storm intensification and extreme events such as high-intensity waves and storm surges on Latin American coasts, resulting in ecosystem, economic, and infrastructure losses. Projections indicate a rise in the population inhabiting Low Elevation Coastal Zones (LECZ) by the century’s end, emphasizing the urgent need for effective management and planning. Community engagement in erosion monitoring and adaptation programs is crucial for addressing these challenges and developing robust, sustainable, long-term adaptation strategies. This study aims to enhance the understanding of coastal erosion in Latin American communities addressing future coastal risks.

Shoreline Change Analysis Using Historical Multispectral Landsat Images of the Pacific Coast of Panama - Ruby Vallarino Castillo; Vicente Negro Valdecantos; Luis Moreno Blasco (Journal of Marine Science and Engineering, 2022)
The shoreline is the interface between sea and land influenced by natural, anthropogenic factors and climate change. The study of the evolution of the shoreline provides information to evaluate accretion or erosion processes. Shoreline erosion represents a threat to the safety of the coastal population, reducing the extension of the beach zone and making human settlements vulnerable to extreme events. This research presents the analysis of the evolution of the shoreline by multispectral images from Landsat satellites and the Digital Shoreline Analysis System (DSAS) of the Pacific Coast of Panama for the period of 1998–2021. The automated shoreline extraction was generated by combining remote sensing techniques, such as the Histogram Threshold Method and the Band Ratio Method, to generate binary images delineating the land and water zone. The most vulnerable zone, due to erosion processes and the exposition of urban areas, corresponds to the zone of Serena beach and Coronado beach with an average negative distance movement of −23.95 m. Finally, it was concluded that there is a general tendency of erosion processes in the study zone with a rate for long-term analysis of −1.12 m/y (zone I), −1.01 m/y (zone II), and −1.08 m/y (zone III).

Seaweed ethnobotany of eastern Sorsogon, Philippines - Richard V. Dumilag; Teresa Haide R. Belgica; Lynn C. Mendoza; Janet M. Hibay; Abel E. Arevalo; Mark Ariel D. Malto; Elden G. Orgela; Mabille R. Longavela; Laurence Elmer H. Corral; Ruby D. Olipany; Caesar Franz C. Ruiz; Cynthia B. Mintu; et al. (Algae, 2022)
Knowledge on the seaweeds of eastern Sorsogon in the Philippines is uneven. Not only is eastern Sorsogon among the areas of high seaweed diversity but locals there have interacted with seaweeds for ages. Despite seaweeds’ assumed importance to Sorsoganon, ethnobotanical records are missing. In this study, we documented the traditional knowledge on seaweed use and determined the rate of knowledge transmission among the locals of eastern Sorsogon. Vernacular names and modes of preparation were given of the 12 identified species bearing culinary and medicinal importance. Ten species were eaten while three were used therapeutically. Based on ethnobotanical indices, Caulerpa chemnitzia ecad turbinata and Gelidiella acerosa were the most important seaweeds. The least cited was Caulerpa racemosa. Our study demonstrated that most of the seaweed resources in eastern Sorsogon remain largely untapped, as the identified ethnotaxa were only about 5% of the total seaweed species diversity reported for the area. The seaweed knowledge in eastern Sorsogon appeared to be homogenous across age groups with primary sources of knowledge biased towards female relatives (mothers and grandmothers) and to children as inheritors. Cessation of seaweed knowledge may come at a potential cost, as a significant fraction of the population did not transmit their knowledge to others. Our study furthered the interest in providing sophisticated resource management recommendations that consider the relationships of traditional and scientific knowledge of seaweed selection and use in eastern Sorsogon and beyond.

Hydrogen Sulfide Production with a Microbial Consortium Isolated from Marine Sediments Offshore - Roberto Briones-Gallardo; Muriel González-Muñoz; Itza García-Bautista; David Valdés-Lozano; Tanit Toledano-Thompson; Erik Polanco-Lugo; Renata Rivera-Madrid; Ruby Valdez-Ojeda (Journal of Marine Science and Engineering, 2022)
Hydrogen, electric energy production, and metal toxic bioremediation are some of the biotechnological applications of sulfate-reducing organisms, which potentially depend on the sulfide produced. In this study, offshore of Yucatan, the capacity to produce hydrogen sulfide using microbial consortia from marine sediment (SC469, PD102, SD636) in batch reactors was evaluated. Kinetic tests were characterized by lactate oxidation to acetate, propionate, CO2 and methane. The inoculum SC469, located in open-ocean, differed strongly in microbial diversity and showed better performance in substrate utilization with the highest hydrogen sulfide production (246 mmolg−1 VSS) at a specific hydrogen sulfide rate of 113 mmol g−1 VSS d−1 with a 0.79 molar ratio of sulfate/lactate. Sulfate-reducing microbial consortia enriched in the laboratory from marine sediments collected offshore in Yucatan and with a moderate eutrophication index, differed strongly in microbial diversity with loss of microorganisms with greater capacity for degradation of organic macromolecules. The sulfate-reducing microorganisms were characterized using Illumina MiSeq technology and were mainly Desulfomicrobium, Clostridium and Desulfobacter.